INTERANNUAL VARIATIONS OF ZONAL MEAN TEMPERATURE IN THE SOUTHERN HEMISPHERE STRATOSPHERE : WITH REFERENCE TO THE ANTARCTIC OZONE DEPLETION - カワヒラ, コウジ; ヒロオカ, トシヒコ; KAWAHIRA, Kohji; HIROOKA, Toshihiko (National Institute of Polar Research, 1987)
P(論文) Interannual variations of the zonal mean temperature in the Antarctic lower stratosphere are analyzed for the past six years from 1980 to 1985 by using NMC data. It is found that the Antarctic polar stratosphere tends to cool not only in spring but also in all seasons, remarkably in the polar region. The analysis of the meridional gradient of the zonal mean temperature shows such an interesting feature that the period of temperature decrease toward the pole in winter has become longer and longer in recent years in accord with the Antarctic ozone depletion. From these evidences, the interrelation between the temperature decline and the ozone depletion is considered as follows : Slight cooling induced by the effect of increasing CO_2 can form the polar stratospheric clouds, and more clouds are formed by its radiative cooling effect. Hence, enhanced cooling in the polar region can induce the ozone depletion due to less poleward transport of ozone by planetary waves, which become less active in the polar region due to trapping by long-persistent strong westerlies. departmental bulletin paper